APOBEC3 enzymes restrict marginal zone B cells - Beck-Engeser, Gabriele B.; Winkelmann, Rebecca; Wheeler, Matthew L.; Shansab, Maryam; Yu, Philipp; Wuensche, Sarah; Walchhuetter, Anja; Metzner, Mirjam; Vettermann, Christian; Eilat, Dan; Defranco, Anthony; Jäck, Hans-Martin; et al. (European Journal of Immunology, 2015)
In general, a long-lasting immune response to viruses is achieved when they are infectious and replication competent. In the mouse, the neutralizing antibody response to Friend murine leukemia virus is contributed by an allelic form of the enzyme Apobec3 (abbreviated A3). This is counterintuitive because A3 directly controls viremia before the onset of adaptive antiviral immune responses. It suggests that A3 also affects the antibody response directly. Here, we studied the relative size of cell populations of the adaptive immune system as a function of A3 activity. We created a transgenic mouse that expresses all seven human A3 enzymes and compared it to WT and mouse A3-deficient mice. A3 enzymes decreased the number of marginal zone B cells, but not the number of follicular B or T cells. When mouse A3 was knocked out, the retroelement hitchhiker-1 and sialyl transferases encoded by genes close to it were overexpressed three and two orders of magnitude, respectively. We suggest that A3 shifts the balance, from the fast antibody response mediated by marginal zone B cells with little affinity maturation, to a more sustained germinal center B-cell response, which drives affinity maturation and, thereby, a better neutralizing response.
EVALuna2:13616